2008
DOI: 10.3102/0002831207312908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Effects of a Research-Based Preschool Mathematics Curriculum

Abstract: A randomized-trials design was used to evaluate the effectiveness of a preschool mathematics program based on a comprehensive model of research-based curricula development. Thirty-six preschool classrooms were assigned to experimental (Building Blocks), comparison (a different preschool mathematics curriculum), or control conditions. Children were individually pre- and posttested, participating in 26 weeks of instruction in between. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
1
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(239 citation statements)
references
References 51 publications
(32 reference statements)
8
219
1
11
Order By: Relevance
“…The researchers found that high-quality learning experiences for students at early grades result in better performance in higher grades [5].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that high-quality learning experiences for students at early grades result in better performance in higher grades [5].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Students in the experimental and control group of mathematics course will be pre-tested and post-tested through a researcher's developed test, based on the standardized test called Research-Based Early Mathematics Assessment (REMA) developed by Clements et al [5] From the pool of 199 items of REMA, the researcher will pick and modify 13 items to assess nursery students' mathematics learning. With the help of teachers, the researcher will pre-test and post-test control and experimental groups of students in English course by converting mathematics items, adopted by REMA, into English items.…”
Section: Instrumentationmentioning
confidence: 99%
“…Bemprechat (1992) has proposed that at-risk students, in particular, need educational scaffolding because they may be less likely to receive academic socialization from their home environments. While the importance of scaffolding math instruction for at-risk students is well established in the preschool and grade school literature (e.g., Clements & Sarama, 2008;Fuligni, Howes, Huang, Hong, & Lara-Cinisomo, 2012;Starkey, Klein, & Wakeley, 2004), Wass, Harland, and Mercer (2011) argued that teaching practices that scaffold instruction should be more widely applied to college settings. In our study, we use the concept of scaffolding to better understand the changes to math course pathways and instruction for at-risk developmental students in community college settings.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several bodies of research have continued to refine their models and test validity and reliability around this topic and have shown experimentally that such knowledge contributes to mathematics achievement (Carpenter, Fennema, Peterson, Chiang, & Loef, 1989;Clements & Sarama, 2008;Hill, Rowan, & Ball, 2005;Starkey, Klein, Clements, & Sarama, 2005).…”
Section: Using Developmental Progressionsmentioning
confidence: 99%